Valdesiana curiosa: a remarkable new genus and species of Clivinematini (Hemiptera: Miridae: Deraeocorinae) from Argentina, and a key to Argentinean genera and species - Carpintero, Diego Leonardo; Dellapé, Pablo Matías; Cheli, German (Zootaxa, 2008)
A remarkable new genus and species of Clivinematini is described. The holotype was collected in Península Valdés, Chubut Province, Argentina. Phylogenetic affinities and some biogeographical notes are discussed. Photographs and a key to known Argentinean genera and species of Clivinematini are provided.